Effects of ocean acidification on fatty acid composition in the Antarctic snail Neobuccinum eatoni - Servetto, Natalia; De Troch, Marleen; Alurralde, Gastón; Ferrero, Luciana; de Aranzamendi, M. Carla; Sahade, Ricardo (Frontiers in Marine Science, 2025)
IntroductionOcean acidification (OA), resulting from the absorption of increasing atmospheric CO2 by the oceans, represents a major threat to marine organisms. Despite growing concern, the biochemical responses of Antarctic species to OA remain poorly understood.MethodsThis study investigated the impact of OA (pH 7.70 ± 0.09) on the fatty acid (FA) composition of the Antarctic snail Neobuccinum eatoni over a two-month experimental period (December 2015–March 2016). Fatty acid profiles were analyzed in multiple tissues to assess potential alterations induced by low-pH (LpH) conditions.ResultsSignificant tissue-specific changes in FA composition were detected, particularly in the mantle and gill. Under LpH exposure, notable modifications occurred in long-chain polyunsaturated fatty acids (LC-PUFAs) such as 22:5n-3, 22:6n-3, and 24:5n-6. Elevated LC-PUFA levels in the mantle suggested a compensatory response to oxidative stress, while shifts in the n-3/n-6 ratios in the gill pointed to potential alterations in immune and anti-inflammatory functions.DiscussionIndicators of homeoviscous adaptation (HVA), including PUFA/SFA ratios and mean chain length (MCL), revealed biochemical strategies used by N. eatoni to maintain membrane fluidity under acidified conditions. This study provides the first evidence of FA-based responses to elevated pCO₂ in an Antarctic gastropod, highlighting the potential of fatty acids as sensitive biomarkers of physiological adaptation to environmental stressors.